Efficient Low‐Grade Heat Harvesting Enabled by Tuning the Hydration Entropy in an Electrochemical System. Issue 13 (17th February 2021) - Gao, Caitian; Liu, Yezhou; Chen, Bingbing; Yun, Jeonghun; Feng, Erxi; Kim, Yeongae; Kim, Moobum; Choi, Ahreum; Lee, Hyun‐Wook; Lee, Seok Woo
Abstract: Harvesting of low‐grade heat (<100 °C) is promising, but its application is hampered by a lack of efficient and low‐cost systems. The thermally regenerative electrochemical cycle (TREC) is a potential alternative system with high energy‐conversion efficiency. Here, the temperature coefficient (α), which is a key factor in a TREC, is studied by tuning the hydration entropy of the electrochemical reaction. The change of α in copper hexacyanoferrate (CuHCFe) with intercalation of different monovalent cations (Na +, K +, Rb +, and Cs + ) and a larger α value of −1.004 mV K −1 being found in the Rb + system are observed. With a view to practical application, a full cell is constructed for low‐grade heat harvesting. The resultant ηe is 4.34% when TREC operates between 10 and 50 °C, which further reaches 6.21% when 50% heat recuperation is considered. This efficiency equals to 50% of the Carnot efficiency, which is thought to be the highest ηe reported for low‐grade heat harvesting systems. This study provides a fundamental understanding of the mechanisms governing the TREC, and the demonstrated efficient system paves the way for low‐grade heat harvesting. Abstract : The temperature coefficient is optimized by tuning the hydration entropy during cation intercalation with Prussian blue analogues. A high thermal energy conversion efficiency of 50% Carnot efficiency is obtained in the thermally regenerative electrochemical cycle in the very low temperature range of 10–50 °C. This demonstrated efficient system paves the way for low‐grade heat harvesting.